Mortality and Morphological Changes in Aedes aegypti Larvae by Bacillus thuringiensis and Serratia marcescens: Mortalitas dan Perubahan Morfologi Larva Aedes aegypti oleh Bacillus thuringiensis dan Serratia marcescens - Yulia Sari, Umi; Rosa, Emantis; Handayani, Kusuma; Busman, Hendri (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2025)
The use of biolarvicides is an alternative biological agent to replace synthetic insecticides, namely entomopathogenic bacteria. The purpose of this study was to determine the potential of Bacillus thuringiensis and Serratia marcescens extracts on mortality and morphological changes in Aedes aegypti larvae. This study was a 2-factor experimental study using a Randomized Block Design (RBD). The first factor, the type of entomopathogenic bacteria, namely B. thuringiensis and S. marcescens. The second factor, the concentration of bacterial extracts (60 mL, 70 mL, 80 mL), negative control (sterile distilled water). Mortality data were processed using ANOVA at the 5% level. The results showed that the administration of B. thuringiensis and S. marcescens extracts caused mortality and morphological changes in Ae. aegypti larvae. B. thuringiensis at concentrations of 60 mL, 70 mL, and 80 mL caused 100% larval mortality, while S. marcescens at concentrations of 60 mL resulted in 70%, 53%, and 50% at concentrations of 70 mL and 80 mL, respectively. Morphological changes in larvae were indicated by changes in color, texture, and damage to the digestive system. It was concluded that B. thuringiensis has the highest potential as an entomopathogenic agent compared to S. marcescens in causing mortality and morphological changes in Ae. aegypti larvae.